2014
DOI: 10.12691/ajmr-2-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>Cryptosporidium </i><i>o</i><i>ocyts </i>in Commonly Consumed Fresh Salad Vegetables

Abstract: The aim of this study was to determine the degree of contamination caused by Cryptosporidium oocyts in regularly consumed salad vegetables sold at various wholesale and retail markets in northern part of Bangladesh. A total number of 165 samples of salad vegetables collected from different wholesale and retail markets were examined for detection of Cryptosporidium oocysts using sucrose flotation medium of 1.18 specific gravity and Ziehl Neelsen staining technique with some modifications. Cryptosporidium oocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
2
16
1
Order By: Relevance
“…The occurrence of parasites of importance for human health on fruits and vegetables in Nigeria may be attributable to contamination arising from parasites eggs, oocysts and larvae from the environment and water used for irrigation and washing of fruits and vegetables, poor hygienic practices by food handlers as well as indiscriminate defecation by domestic and wild animals. The parasites identified in this study were reported in other parts of Africa [21,23,34,35] and other parts of the world [25,26,36]. The pooled prevalence estimate of 32.4% revealed by this study is higher than the 13.5 [23] and 15.5% [25] reported by individual surveillance studies from Sudan and Iran respectively.…”
Section: Data Extractioncontrasting
confidence: 53%
“…The occurrence of parasites of importance for human health on fruits and vegetables in Nigeria may be attributable to contamination arising from parasites eggs, oocysts and larvae from the environment and water used for irrigation and washing of fruits and vegetables, poor hygienic practices by food handlers as well as indiscriminate defecation by domestic and wild animals. The parasites identified in this study were reported in other parts of Africa [21,23,34,35] and other parts of the world [25,26,36]. The pooled prevalence estimate of 32.4% revealed by this study is higher than the 13.5 [23] and 15.5% [25] reported by individual surveillance studies from Sudan and Iran respectively.…”
Section: Data Extractioncontrasting
confidence: 53%
“…Different agronomic practices can contaminate vegetables in various stages. Contamination occurs mostly before harvesting, either by contaminated manure, sewage, irrigation water, and wastewater from livestock operations or directly from wild and domestic animals or during harvesting, transport, processing, distribution, and marketing or even at home (Eraky et al 2014; Rahman et al 2014; Pagadala et al 2015; Maffei et al 2016). The use of wastewater for irrigation affects the quality of RSV and human health.…”
Section: Introductionmentioning
confidence: 99%
“…in 200 vegetable samples marketed in Zaria metropolis, Nigeria with no difference between contamination rates in lettuce (48%), spinach (40%), and waterleaf (36%). Accordingly, Rahman et al (2014) have reported that the rates of Cryptosporidium oocysts did not differ among the total examined vegetables in Bangladesh.…”
Section: Discussionmentioning
confidence: 90%